2022
DOI: 10.1371/journal.pone.0266285
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tuberculosis among PLHIV on antiretroviral therapy who initiated isoniazid preventive therapy: A multi-center retrospective cohort study

Abstract: Introduction Isoniazid preventive therapy (IPT) is effective in treating tuberculosis (TB) infection and hence limiting progression to active disease. However, the durability of protection, associated factors and cost-effectiveness of IPT remain uncertain in low-and-middle income countries, Uganda inclusive. The Uganda Ministry of health recommends a single standard-dose IPT course for eligible people living with HIV (PLHIV). In this study we determined the incidence, associated factors and median time to TB d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“… 5 Children 421 10412.15 52 0.499 38. East Africa Kazibwe A, et al [ 97 ], 2022 Uganda Retr. 5 Both 2634 9696.73 22 0.227 39.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Children 421 10412.15 52 0.499 38. East Africa Kazibwe A, et al [ 97 ], 2022 Uganda Retr. 5 Both 2634 9696.73 22 0.227 39.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the relationship between WHO clinical stages and tuberculosis, 21 studies were reviewed. The relationship was found to be positive in 10 studies [ 61 , 66 , 75 , 76 , 81 , 86 , 88 , 90 , 97 , 98 ], negative in one study [ 99 ], and insignificant in the remaining ten studies. The random effect model meta-analysis revealed that patients with WHO clinical stages ¾ were 2.29 times more likely to develop tuberculosis than patients with WHO clinical stages ½ (AHR = 2.29, 95% CI: 1.34–3.23).…”
Section: Resultsmentioning
confidence: 99%